Congenital plaque-like glomangioma: report of two cases - Nivea Godinho Alves de Souza; Gisele Alborghetti Nai; Gláucia Ferreira Wedy; Marilda Aparecida Milanez Morgado de Abreu (Sociedade Brasileira de Dermatologia, 2017)
Abstract: Glomus tumors are rare hamartomas that originate from the glomus body. These tumors can be divided into solitary and multiple, the latter also known as glomangioma. We report the case of two patients with a rare variety of glomangioma called congenital plaque-like glomangioma. It presents as numerous red to bluish compressible papules, that increase in size in proportion with the weight and height growth of the child. Diagnostic confirmation is with histopathology and the treatment is surgical.